Effect of Rhizobial Inoculation on Nitrogen Fixation in Albizia lebbek and Dalbergia sissoo - Kaur, Ajeet; Chaukiyal, S. P.; Pandey, P. C.; Pokhriyal, T. C. (Indian Forester, 2015)
Rhizobia were isolated from active nodules of Albizia lebbek and Dalbergia sissoo from different sources and confirmed against nodulation test. Several other physiological and biochemical tests were also performed. They were then multiplied in Yeast Extract Mannitol (YEM) broth and inoculated into their respective A. lebbek and D. sissoo seedlings. These were maintained under pot culture conditions in the glass house for few months to study the effect of inoculation treatments on nodulation, nitrogen fixation and biomass production. It was found that A. lebbek seedlings inoculated with rhizobial isolates of Lalpani gave the highest nodular biomass, specific and total nitrogenase activity. In case of D. sissoo, isolate from Asharori resulted in highest nitrogenase activity under pure culture conditions and maximum nodular number, nodular biomass, collar diameter and plant height as compared to other inoculation treatments. No relationship between nitrogenase activities of rhizobial isolates under pure culture and symbiotic conditions was observed. It may be concluded that both the isolates of Lalpani and that of Asharori may be utilized for the forestry programmes of planting A. lebbek and D. sissoo respectively.